4
$\begingroup$

Suppose $x_0,y_0$ are reals such that $x_0^2+y_0^2>0.$ Suppose $x(t)$ and $y(t)$ satisfy the following:

  • $\frac{dx}{dt} = (x-y)(1-x^2-y^2),$
  • $\frac{dy}{dt} = (x+y)(1-x^2-y^2),$
  • $x(0) = x_0,$
  • $y(0) = y_0.$

I am asked to find $\lim_{t\to\infty}x(t).$

Dividing the two differential equations, we have $$\frac{dy}{dx} = \frac{x+y}{x-y} = \frac{1 + \frac{y}{x}}{1-\frac{y}{x}}.$$ Let $v(x)=\frac{y}{x},$ so that $y = xv(x),$ and $$\frac{dy}{dx} = v + x\frac{dv}{dx}.$$ This implies that $$x\frac{dv}{dx} = \frac{1+v}{1-v} - v = \frac{1+v^2}{1-v}.$$ Rearranging and integrating, we get $$\log(x) = \arctan(v)-\frac{1}{2}\log(1+v^2)+c,$$ so $$\log(x) = \arctan\left(\frac{y}{x}\right)-\frac{1}{2}\log\left(1+\left(\frac{y}{x}\right)^2\right)+c.$$ By writing $1+\left(\frac{y}{x}\right)^2$ as $\frac{x^2+y^2}{x^2},$ we can simplify the above equation to $$\frac{1}{2}\log(x^2+y^2) = \arctan\left(\frac{y}{x}\right) + c.$$

However, I'm not sure how to proceed from this implicit equation. Any help would be much appreciated!

$\endgroup$
  • 1
    $\begingroup$ Use polar coordinates... $\endgroup$ – player100 Aug 24 '18 at 4:02
  • $\begingroup$ @player100 well using polar, I can get $r = Ae^\theta,$ but I'm not sure how that helps me find $\lim_{t \to \infty}x(t)..?$ $\endgroup$ – dhk628 Aug 24 '18 at 4:45
  • 1
    $\begingroup$ Note that $(r^2)'=(x^2+y^2)'=2(xx'+yy')$. And you can substitute your equations for $x'$ and $y'$ into that expression, and simplify. $\endgroup$ – player100 Aug 24 '18 at 4:58
  • $\begingroup$ Eliminating $t$ leads you nowhere as you are asked the limit for $t\to\infty$. $\endgroup$ – Yves Daoust Aug 24 '18 at 6:34
  • $\begingroup$ The title was wrong (you are not asked to solve the system, only to find the limit of $x(t)$) and uninformative, please see modified version. $\endgroup$ – Did Aug 24 '18 at 6:44
2
$\begingroup$

If you only want to compute the limit, you don't even need to solve the equation explicitly (at least for $r$).

Following @player100's suggestion, you can transform the system into $$ \begin{cases} \dot r = r(1-r^2)\\ \dot \theta = 1-r^2 \end{cases}, $$ with $r^2 = x^2+y^2$ and $\theta = \arctan\frac{y}{x}.$

Then we can observe that our system rests at the origin as well as on the unit circle. Since $\dot r > 0$ when $0 < r < 1,$ and $\dot r < 0$ when $r>1$, we may conclude that any solution starting in $(x_0,y_0)$ with $x_0^2+y_0^2 > 0$ will be attracted to the unit circle, so that $$\lim_{t \to \infty} r(t) = 1.$$

Hence our limit becomes $$ \lim_{t\to \infty} x(t) = \lim_{t\to \infty} r(t)\cos\theta(t) = \lim_{t\to \infty} \cos\theta(t) = \cos \left(\lim_{t\to \infty}\theta(t)\right). $$ Now \begin{align} \theta(t) - \theta(t_0) &= \int_{t_0}^t \dot\theta(s) \, ds = \int_{t_0}^t 1-r(s)^2 \, ds, \end{align} and changing the integration variable to $u = r(s),$ so that $$du = \dot r(s) \, ds = r(s)(1-r(s)^2) \, ds = u(1-u^2) \, ds,$$ we obtain \begin{align} \int_{t_0}^t 1-(r(s))^2 \, ds &= \int_{r(t_0)}^{r(t)} \frac{1}{u} \, du = \log(r(t))-\log(r(t_0)). \end{align} This gives \begin{align} \lim_{t\to \infty}\theta(t) &= \lim_{t\to \infty}\theta(t) - \theta(t_0) + \theta(t_0) = \lim_{t\to \infty} \log(r(t))-\log(r(t_0)) + \theta(t_0)\\ &= \log(1)-\log(r(t_0)) + \theta(t_0) = \arctan{\frac{y_0}{x_0}} - \log\sqrt{x_0^2+y_0^2}, \end{align} so that $$\lim_{t\to \infty} x(t) = \cos \left( \arctan{\frac{y_0}{x_0}} - \log\sqrt{x_0^2+y_0^2} \right). $$

$\endgroup$
3
$\begingroup$

We first pass to polar coordinates, viz:

$x = r\cos \theta; \; y = r \sin \theta; \tag 1$

$\dot x = \dot r \cos \theta - r\dot \theta \sin \theta; \tag 2$

$\dot y = \dot r \sin \theta + r \dot \theta \cos \theta; \tag 3$

$\begin{pmatrix} \dot x \\ \dot y \end{pmatrix} = \begin{bmatrix} \cos \theta & -r \sin \theta \\ \sin \theta & r\cos \theta \end{bmatrix} \begin{pmatrix} \dot r \\ \dot \theta \end{pmatrix}; \tag 4$

$\begin{bmatrix} \cos \theta & -r \sin \theta \\ \sin \theta & r\cos \theta \end{bmatrix}^{-1} = \dfrac{1}{r} \begin{bmatrix} r\cos \theta & r\sin \theta \\ -\sin \theta & \cos \theta \end{bmatrix} ; \tag 5$

$\begin{pmatrix} \dot r \\ \dot \theta \end{pmatrix} = \dfrac{1}{r} \begin{bmatrix} r\cos \theta & r\sin \theta \\ -\sin \theta & \cos \theta \end{bmatrix}\begin{pmatrix} \dot x \\ \dot y \end{pmatrix}; \tag 6$

$\dot x = (x - y)(1 - x^2 - y^2) = r(\cos \theta - \sin \theta)(1 - r^2); \tag 7$

$\dot y = (x + y)(1 - x^2 - y^2) = r(\cos \theta + \sin \theta)(1 - r^2); \tag 8$

$\begin{pmatrix} \dot r \\ \dot \theta \end{pmatrix} = \dfrac{1}{r} \begin{bmatrix} r\cos \theta & r\sin \theta \\ -\sin \theta & \cos \theta \end{bmatrix}\begin{pmatrix} r(\cos \theta - \sin \theta)(1 - r^2) \\ r(\cos \theta + \sin \theta)(1 - r^2)\end{pmatrix}$ $= (1 - r^2) \begin{bmatrix} r\cos \theta & r\sin \theta \\ -\sin \theta & \cos \theta \end{bmatrix} \begin{pmatrix} \cos \theta - \sin \theta \\ \cos \theta + \sin \theta \end{pmatrix} = (1 - r^2) \begin{pmatrix} r \\ 1 \end{pmatrix}; \tag{10}$

$\dot r = r(1 - r^2); \tag{11}$

$\dot \theta = 1 - r^2. \tag{12}$

Since

$x_0^2 + y_0^2 > 0, \tag{13}$

we have

$r_0^2 = x_0^2 + y_0^2 > 0 \Longrightarrow r_0 > 0; \tag{14}$

by (11),

$0 < r < 1 \Longrightarrow \dot r > 0; \tag{15}$

$1 < r \Longrightarrow \dot r < 0; \tag{16}$

$r = 1 \Longrightarrow \dot r = 0; \tag{17}$

it is relatively easy to see that (14)-(17) in concert imply that

$\displaystyle \lim_{t \to \infty} r = 1; \tag{18}$

also, (11) and (12) together yield

$r \ne 0 \Longrightarrow \dot{(\ln r)} = \dfrac{\dot r}{r} = 1 - r^2 = \dot \theta, \tag{19}$

whence, integrating over $t$,

$\ln r - \ln r_0 = \theta - \theta_0, \tag{20}$

or

$\theta = \ln r - \ln r_0 + \theta_0, \tag{21}$

and so via (18)

$\displaystyle \lim_{t \to \infty} \theta = \lim_{t \to \infty} \ln r - \ln r_0 + \theta_0 = \theta_0 - \ln r_0; \tag{22}$

finally,

$\displaystyle \lim_{t \to \infty} x(t) = \lim_{t \to \infty} ( r \cos \theta) = (\lim_{t \to \infty} r)( \lim_{t \to \infty} \cos \theta) = \cos (\theta_0 - \ln r_0). \tag{23}$

$\endgroup$
  • 1
    $\begingroup$ +1 really nice and complete answer @Robert $\endgroup$ – Isham Aug 24 '18 at 13:40
  • 1
    $\begingroup$ @Isham: thank you sir! $\endgroup$ – Robert Lewis Aug 24 '18 at 14:26
2
$\begingroup$

Let $r^2 = x^2+y^2$, $x = rcos\theta$, and $y = rsin\theta$.

Then, you get the following equations: $$\begin{align}\frac{dr}{dt} &= r(1-r^2) \\ \frac{d\theta}{dt} &= (1-r^2) \end{align}$$

The solution to the first equation is: $r^2=\frac{ke^{2t}}{1+ke^{2t}}$, where $k=\frac{r^2_0}{1-r_0^2}$.

Then, the solution to the second equation is: $\theta-\theta_0=log\ \frac{r}{r_0}$,

where $r_0^2=x_0^2+y_0^2$ and $tan\ \theta_0= \frac{y_0}{x_0}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.